2023
DOI: 10.1093/function/zqad019
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between Neuronal and Astrocytic Calcium Activity in Response to Locomotion in Mice

Abstract: Orchestrated activity of different cell types and their interactions within the brain active milieu provide the cellular basis for brain functions. Locomotion triggers a coordinated response of both neurons and astrocytes in various brain regions. Here we performed calcium (Ca2+) imaging of these two cell types in the somatosensory cortex in head-fixed mice moving on the airlifted platform. Ca2+ activity in astrocytes significantly increased during locomotion from a low baseline level during animal quiescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
3
8
0
Order By: Relevance
“…2g and 2h). These results are consistent with previous studies comparing the time course of astrocyte and neuronal calcium activity at single cell resolution 24 and suggest that these cell types may regulate behavioral processes at different timescales. One interpretation is that astrocyte activity signals a locomotion behavioral state for the striatal circuit and promotes continued coordination of incoming cortical and thalamic sensorimotor information 24,37,46 with dopaminergic neuromodulation and local neuronal processing 47 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2g and 2h). These results are consistent with previous studies comparing the time course of astrocyte and neuronal calcium activity at single cell resolution 24 and suggest that these cell types may regulate behavioral processes at different timescales. One interpretation is that astrocyte activity signals a locomotion behavioral state for the striatal circuit and promotes continued coordination of incoming cortical and thalamic sensorimotor information 24,37,46 with dopaminergic neuromodulation and local neuronal processing 47 .…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies comparing the time course of astrocyte and neuronal calcium activity at single cell resolution 24 and suggest that these cell types may regulate behavioral processes at different timescales. One interpretation is that astrocyte activity signals a locomotion behavioral state for the striatal circuit and promotes continued coordination of incoming cortical and thalamic sensorimotor information 24,37,46 with dopaminergic neuromodulation and local neuronal processing 47 . Reduction of astrocyte calcium activity with dopamine loss would disrupt this process, which in parallel with the well-documented effects of dopamine loss on neuronal intrinsic properties and synaptic structure and function 3 would result in motor dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…The large response of astrocytes may prevent them from fully restoring calcium levels for the next event, leading to a decline in response to electrical stimulation. A similar refractory period was observed in vivo, where astrocytes had a significantly diminished response to a second event [18] and ex-vivo where a decrease in average calcium amplitude was observed after stimulation of astrocytes with baclofen [19]. The astrocytic response exhibits/displays electrical signals even in the absence of a calcium signal.…”
Section: A Electrically Evoked Calcium Signals Are Faster Larger and ...supporting
confidence: 62%
“…This might be associated with a refractory period of calcium signalling in astrocytes that may become evident after the massive calcium release observed after stimulation. Fedotova and colleagues recently proposed an astrocytic refractory period that arises due to the depletion of intracellular calcium stores in astrocytes, which affects consecutive calcium signals [18]. This excludes the use of calcium imaging data to clarify the mechanisms behind its dynamics as the response is inherently different when comparing the first stimuli (baseline) with the response obtained after pharmacological manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…9 ). Interestingly, a recent study has observed centripetal propagation in cortical brain regions 44 ; hence, it is likely that this phenomenon is not restricted to hippocampus.…”
Section: Discussionmentioning
confidence: 94%